Fikih Media Sosial di Indonesia (Studi Analisis falsafah hukum Islam dalam Kode Etik NetizMu Muhammadiyah) - Istiani, Nurul; Islamy, Athoillah (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2020)
This study aims to reveal the philosophical values of Islamic law in the three ethical codes of NetizMu Muhammadiyah. This research is a literature review. The type of Islamic legal research in this study is a philosophical normative Islamic law research with an Islamic legal philosophy approach. The primary data source of this research, namely the NetizMU Muhammadiyah code of ethics), and secondary data using various relevant scientific researches. The theory used is a systems philosophy approach in Islamic law initiated by Jasser Auda.. This study concludes that there are values ​​of Islamic law philosophy in the three NetizMU codes of ethics. First, the value of religious protection (hifz al-din) in the context of making the prophetic social values ​​of religion the main basis for the code of ethics for the use of social media. Second, the value of public benefit (al-maslahat al-ammah) in the code of ethics for the use of social media as a medium for humanization (amar makruf) and liberation (nahi munkar). Third, the value of intellectual protection (hifz al-'aql) in the context of a code of ethics limiting freedom of expression, both in the form of information and communication on social media.